Redescription of the tintinnid ciliate Tintinnopsis fimbriata Meunier, 1919 (Spirotricha, Choreotrichida) from coastal waters of Northern Germany - Agatha, Sabine (2008)
The tintinnid ciliate Tintinnopsis fimbriata Meunier, 1919 is mainly distributed in mesohaline coastal waters of Arctic, temperate, and subtropical regions. Since its cytological features were unknown, the species is redescribed and neotypified from material collected in coastal waters of the North Sea near the Island of Sylt (Northern Germany), using live observation and protargol impregnation. The species diagnosis is improved to include the new characteristics, e.g., the somatic ciliary pattern comprising a ventral, dorsal, and posterior kinety as well as a right, left, and lateral ciliary field. Due to the complex somatic ciliary pattern, T. fimbriata belongs to a diverse group of highly developed tintinnids with which it shares the hypoapokinetal development of the oral primordium posterior to the lateral ciliary field.